Animated Video Media Contains Tri Kaya Parisudha on The Theme of My Environment - Novia Kadek Widyastuti Rahayu; Anak Agung Gede Agung (Mimbar Ilmu, 2023)
PAUD teachers experience problems and difficulties when developing appropriate learning media when teaching. This research aims to develop Tri Kaya Parisudha's Animated Video Media on the My Environment Theme for PAUD. This type of research is developed using the ADDIE model. The product was tested by 1 learning content expert, 1 instructional design expert, 1 learning media expert, as well as with research subjects 3 individual trial students, 6 small group trial students, and an effective test using 19 students. The data obtained is quantitative data by collecting data using a questionnaire/questionnaire and an observation questionnaire (non-test). The data analysis technique used is quantitative descriptive analysis and inferential statistics. The study's results, firstly, the design of animated video media using the ADDIE development model with the assessment results by design experts with a very good percentage. Second, the validity of the animated video media shows the results of the validity according to the experts and research subjects having good and very good categories so that the developed product is feasible to use. Third, the effectiveness of video animation media based on the results of the t-test shows that the video animation media based on Tri Kaya Parisudha is effectively applied to the theme of my environment in group B PAUD children.